A PRELIMINARY STUDY OF LICHEN DIVERSITY IN GUNUNG HALIMUN SALAK NATIONAL PARK - Fandri Sofiana Fastanti; Dewi Susan; Yayan Supriyanti; Sutikno Sutikno (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2020)
Lichen is an associated organism between fungi and algae. The research of lichen in Indonesia still inadequate, especially on the island of Java. Gunung Halimun Salak National Park is one of conservation area in West Java. The diversity of lichen in this area has never been reported. This study aims to provide preliminary information of lichen diversity in Gunung Halimun Salak National Park. This research was conducted in October 2019. All of the lichen specimens were carried out along the main road of Gunung Halimun Salak National Park. A total of 30 species were found in this study belongs to 18 genera and 10 families. The most dominant lichen species from Graphidaceae with crustose as growth form.